Damage Prediction in the Wire Drawing Process - Cruchaga-Ssa., M (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this study, the prediction of damage in the wire drawing process of 2011 aluminum alloy was investigated through both experimental and numerical methods. A comprehensive experimental setup was designed involving 20 cases of wire drawing with varying die angles ((Formula presented.), (Formula presented.), (Formula presented.), (Formula presented.), and (Formula presented.)) and reductions (21%, 29%, 31%, and 38%). Each case was tested three times, and the drawing forces, as well as occurrences of wire breakage, were recorded. The mechanical behavior of the material was firstly characterized using uniaxial tensile tests, whose results were used to determine the material parameters of both the hardening Voce law and those of uncoupled and coupled damage models. Then, the numerical simulations of the wire drawing process were performed using a finite element model, accounting for axisymmetric conditions and mesh convergence analysis to ensure accuracy. The previously characterized damage models were applied to evaluate their fracture prediction capabilities. A novel presentation method using three-dimensional graphs was employed to indicate the level of damage for each angle and reduction, providing greater sensitivity and insight into the damage values. Good agreement between the experimental and numerical data was demonstrated for the bilinear coupled damage model, validating its effectiveness. This study contributes to a better understanding of damage prediction in the wire drawing process, with implications for improving industrial practices and material performance evaluations. © 2024 by the authors.